Specificity of the Linear Array HPV Genotyping Test for detecting human papillomavirus genotype 52 (HPV-52) - Oštrbenk, Anja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2014)
Introduction: HPV-52 is one of the most frequent human papillomavirus (HPV) genotypes causing significant cervical pathology. The most widely used HPV genotyping assay, the Roche Linear Array HPV Genotyping Test (Linear Array), is unable to identify HPV- 52 status in samples containing HPV-33, HPV-35, and/or HPV-58. Methods: Linear Array HPV-52 analytical specificity was established by testing 100 specimens reactive with the Linear Array HPV- 33/35/52/58 cross-reactive probe, but not with the HPV-33, HPV-35, and/or HPV-58 individual probes, using an HPV-52%specific real-time PCR assay with a detection level of 3.9 DNA copies/reaction. In addition, we established the prevalence of HPV-52 in 49 samples reactive with the Linear Array HPV-33/35/52/58 cross-reactive probe, but containing either HPV-33, HPV-35, and/or HPV- 58 using the same approach. Results: The HPV-52%specific assay detected HPV-52 in all 100 samples reactive with the Linear Array HPV-33/35/52/58 cross-re - active probe, but not with the HPV-33, HPV-35, and/or HPV-58 probes. The presence of up to six other HPV genotypes did not influ - ence the HPV-52 analytical performance of Linear Array. Only 6/49 (12.2%) samples reactive with the Linear Array HPV-33/35/52/58 cross-reactive probe, but containing either HPV-33, HPV-35 or/and HPV-58, were HPV-52 positive. Conclusions: Linear Array is a highly reliable test for detecting HPV-52 in the absence of genotypes HPV-33, HPV-35, and HPV-58. Additional testing using an HPV-52%specific test is necessary when HPV-33, HPV-35, and/or HPV-58 are present in the sample.
Keywords: človeški papilomavirus; genotipizacija; genotyping; human papillomaviruses; papillomavirus genotype 52; papiloma genotip 52